Upper gastrointestinal cancer pathology reporting: a regional audit to compare standards with minimum datasets. Issue 7 (25th June 2004) - King, P M; Blazeby, J M; Gupta, J; Alderson, D; Moorghen, M
Abstract : Aims: Accurate pathological (pTNM) staging of oesophageal and gastric cancer provides important prognostic information. The aim of this study was to compare the standard of pathology reporting of oesophageal and gastric cancer resections from a cancer network with standards set by the Royal College of Pathologists. Methods: All reports for oesophageal and gastric cancer resections from the five hospitals in the cancer network in 2001 were collected. Individual items of information were compared with minimum datasets provided by the Royal College of Pathologists. Items were classified as "complete", "partially complete", or "absent". Results: One hundred and ten reports were audited (54 oesophageal and 56 gastric). Fourteen gastric and 17 oesophagectomy reports were over 75% complete. Clinically important missing data occurred most frequently for the pM component of TNM staging (pMx omitted in 87 reports) and completeness of resection expressed as a bold statement (absent in 50 reports). Twelve reports could not be classified because the specimen contained no residual tumour after neoadjuvant treatment. Conclusion: The use of a standard proforma for reporting upper gastrointestinal cancers based on a minimum dataset provided by the Royal College of Pathologists is recommended, with modifications to allow for specimens with no tumour after neoadjuvant treatment.